Real-Time Monitoring and Defect Detection of Laser Scribing Process of CIGS Solar Panels Utilizing Photodiodes - Valtonen Veli-Matti; Roozbahani Hamid; Alizadeh Marjan; Handroos Heikki; Salminen Antti (Institute of Electrical and Electronics Engineers, 2022)
Laser scribing is developing rapidly in industrial applications as a method of material processing, especially in areas that require high levels of precision. This technology provides functionality and efficiency improvements in the manufacturing of solar panels. Due to the premium quality and speed requirements of the laser scribing technology, monitoring of this process in real-time is critical in order to promptly detect defects in the manufacturing process. However, common monitoring systems have been developed for other laser processes, like laser welding, which are noticeably slower than the laser scribing process. The goal of this research was to investigate the possibility of using photodiodes for real-time monitoring of the laser scribing process for Copper Indium Gallium Selenide (CIGS) solar panels. Various monitoring setup configurations were designed, developed, and examined to determine the viable option for implementation as a defect detection platform. Using different photodiode positions, the intensity of the light and the photodiode induced voltage for diffuse and specular reflections were tested, and the practical pros and cons of applying each configuration were analyzed. The capability of the monitoring system to distinct the different layers of the scribed CIGS cell was also examined to assess the penetration depth of the scribe. In addition, by performing several experiments with different scribe thicknesses and analyzing oscilloscope measurements, the optimal placement of the photodiode for accurate tracing of the scribing path was determined and verified. Key aspects of development of such monitoring system for solar panel applications were identified through this research.